2009
DOI: 10.1007/s11483-009-9124-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sterol Type on Structure of Tubules in Sterol + γ-Oryzanol-Based Organogels

Abstract: The mixture of γ-oryzanol with β-sitosterol forms a network of tubules in edible oil that may serve as an alternative to the network of small crystallites of triglycerides occurring in regular oil structuring. The present experiments demonstrate that the tubules vanish at the melting point of the gel. Moreover, a number of alternative sterols (e.g., ergosterol, stigmasterol, cholesterol, cholestanol) can replace sitosterol in the tubules. The tubule diameter varies between 6.7 and 8.0 nm, the wall thickness be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 28 publications
5
69
1
Order By: Relevance
“…In this study, homogenous solutions of γ-oryzanol (see Figure 1 for chemical structure; Tsuno Rice Fine Chemicals, Wakayama, Japan) and tall oil sterol (78.5% β-sitosterol, 10.3% β-sitostanol, 8.7% campesterol, and 3.8% of other minor sterols,7,11 Unilever, The Netherlands) mixtures in sunflower oil (Reddy, NV Vandemoortele, Breda, The Netherlands) were prepared by stirring at ∼90 °C using a magnetic stirrer. The minor sterol compounds present in the tall oil sterol have a very similar chemical structure to the β-sitosterol, and it was recently found that the gelling behavior and structural properties of their organogels with γ-oryzanol are similar to β-sitosterol-γ-oryzanol organogels 7,11.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, homogenous solutions of γ-oryzanol (see Figure 1 for chemical structure; Tsuno Rice Fine Chemicals, Wakayama, Japan) and tall oil sterol (78.5% β-sitosterol, 10.3% β-sitostanol, 8.7% campesterol, and 3.8% of other minor sterols,7,11 Unilever, The Netherlands) mixtures in sunflower oil (Reddy, NV Vandemoortele, Breda, The Netherlands) were prepared by stirring at ∼90 °C using a magnetic stirrer. The minor sterol compounds present in the tall oil sterol have a very similar chemical structure to the β-sitosterol, and it was recently found that the gelling behavior and structural properties of their organogels with γ-oryzanol are similar to β-sitosterol-γ-oryzanol organogels 7,11.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was reported that mixtures of γ-oryzanol and β-sitosterol form translucent, firm, and thermo-reversible gels in sunflower oil even when high structurant concentration is used (i.e., >16%, w / w ) 6 , 7. Bot and coworkers found that the firmness and transparency of the gel depend on the oryzanol–sitosterol ratio 6,7,11. The haziness of the gel decreased with increasing γ-oryzanol concentration and the firmest gel was always obtained at the ratio of ∼60–40 w / w oryzanol–sitosterol 6-8.…”
Section: Introductionmentioning
confidence: 99%
“…Different edible gelators were investigated in the literature, such as: triacylglycerols (TAGs), diacylglycerols (DAGs), monoacylglycerols (MAGs) (Calligaris, Da Pieve, Arrighetti, & Barba, 2010;Da Pieve, Calligaris, Co, Nicoli, & Marangoni, 2010;Ojijo, Neeman, Eger, & Shimoni, 2004), fatty acids and fatty alcohols (Schaink, van Malssen, Morgado-Alves, Kalnin, & van der Linden, 2007), sorbitan tri-stearate and/or lecithin (Pernetti, van Malssen, Kalnin, & Flöter, 2007;Shchipunov, 2001), sterol and γ-oryzanol (Bot, den Adel, Roijers, & Regkos, 2009), waxes (Toro-Vazquez, Morales-Rueda, Ajay Mallia, & Weiss, 2010) and others. Among them, monoglycerides are particularly interesting because, in addition to their gelling ability, they are also responsible of positive health effects (Goldstein & Seetharaman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Duffy et al. (2009) report systems able to form structure in the aqueous phase, and it has been confirmed (Bot & Agterof, 2006; Bot et al. , 2008; 2009a) that β‐sitosterol–γ‐oryzanol fibril systems are quite unique as they are one of the few combinations capable of forming fibril structures in both aqueous and oil systems.…”
Section: Non‐traditional Structurantsmentioning
confidence: 91%